Pengujian Struktur Sepatu Kuda Bahan Komposit Polymeric Foam Berpenguat Fiberglass Menggunakan Uji Impak Jatuh Bebas - -, Mawardi; Syam, Bustami; Muttaqin, Maraghi (Fakultas Teknik UMSU, 2020)
This study aims to determine the mechanical structure of polymeric foam reinforced with fiberglass horseshoes. Observations are focused on the average maximum impact force and the average maximum impact stress obtained from the free fall impact test. Testing the free fall impact structure with an impactor weight of 10 kg on five horseshoe test specimens 1, 2, 3, 4 and 5 with an impact distance of 2.5 meters, 2 meters, 1.5 meters, 1 meter and 0.5 meters, the results are horse shoe test specimens does not experience cracks / broken. The results obtained are in the form of the highest stress on the 1A test specimen with a stress value of 0.154 MPa and the maximum force found in the 1A test specimen of 874.95 N. with an impactor weight of 12.5 kg the test specimen cracks / breaks at a height of 3 m and 2.5 m, resulting in the highest impact stress value in sample 6B of 0.21 MPa and a force of 1185.5 N. then the force and stress will be higher but the level of damage will also be greater.